A Review of the Design of Advanced Binders for High‐Performance Batteries. Issue 45 (16th October 2020) - Zou, Feng; Manthiram, Arumugam
Abstract: Polymer binders as a critical component in rechargeable batteries provide the electrodes with interconnected structures and mechanical strength to maintain the electronic/ionic transfer during battery cycling. The conventional binders, such as polyvinylidene fluoride (PVDF), are not ideal candidates due to their relatively low adhesiveness, weak mechanical strength, and poor functionality for high‐energy‐density batteries with a thick electrode and/or a high‐capacity electrode. Nevertheless, the binder has not yet received the attention that reflects its importance in batteries. The requirements of high energy density batteries make essential the exploration of advanced polymeric binders, which possess particular functions. In this review, state‐of‐the‐art binder design strategies are sorted in terms of the challenges of various electrodes (anodes and cathodes for lithium ion batteries (LIBs) and sulfur cathodes for Li–S batteries), which have been commercialized or have the potential for practical cells. A deep insight into how the polymeric binders improve the cell performance and the design principle of new binders is also provided. Finally, a perspective on the direction of future binder development for high‐energy‐density batteries with long cycle life is presented. Abstract : Advanced binder materials for lithium‐ion batteries (LIBs) are briefly reviewed in this article. The basic strategies for binder design for various electrode materials are summarized, providing a comprehensive insight into advanced binders for high energy density electrodes. A perspective is also provided on future binder development for high‐performance LIBs.